Performance study of mobility support in WiMax networks - Nagarajan Maheswari (2009)
The IEEE 802.16 standards which are the core of the Worldwide Interoperability for Microwave Access (WiMAX) define a system where Mobile Stations (MSs) correspond to end-user equipment and Base Stations (BSs) control activity within a cell range. A cell therefore includes on BS and several MSs which together from a point-to-multipoint infrastructure controlled by the BS. The IEEE 802.16e standard, which has been published in Feb of 2006, has specified the mobility supports in WiMAX networks, which has the potential to replace current 3G cellular networks due to its much higher data transmission rate. As background for the integrated mobility process, IEEE 802.16e-2005 defines Handovers (HO) between different mobile WiMAX networks. A HO is defined as the migration of a MS between air-interfaces of different BSs. The HO process introduces a large number of interactions between the MS and adjacent BSs for the purpose of Scanning, Ranging, Parameter Negotiation and Information Exchanging. In this process, which may take hundreds of milliseconds, the MS leaves its previous channel thus temporally suspending running services. In cellular network, the HO may cause packet losses and service disruptions. The technology and standards of WiMAX is the focus of the thesis paper, and more specially its mobility capabilities. This research proposes a novel handoff scheme for IEEE 802.16e based wireless broadband access networks, to improve the Mobile WiMAX HOs. The proposed handoff scheme, oversimplify the network topology acquisition procedure and thus impair the accuracy of HO. This scheme eliminates the packet loss and minimized handoff delay during HO. We show, by means of simulations, that our solution can effectively reduce the Mobile HO latency and increases the system throughput significantly.